Examining Predictors of Group Leader Self-Efficacy for Preservice School Counselors. Issue 4 (1st October 2016) - Springer, Sarah I.
Abstract : Group counseling is an important treatment modality used to support clients in a variety of therapeutic settings. This article highlights the results of an exploratory study that examined site supervisory factors that predicted group leader self-efficacy for preservice school counselors. Results of multiple regression analyses suggest meaningful relationships between receiving feedback and managing anxiety specific to group leadership (two important aspects inherent in the process of supervision) and preservice school counselors' group leader self-efficacy. Implications for counselor training and supervision are discussed.